THE EFFECT OF DRINKING TURMERIC STEW TOWARDS REDUCING DYSMENORRHEAL PAIN SCALE ON STUDENTS OF SENIOR HIGH SCHOOL 1 OF EAST PAMONA, POSO REGENCY - Adrian Sali; Muhammad Risal (Jurnal Ilmu Kesehatan, 2021)
ABSTRACT Menstrual pain, or dysmenorrhea, is a problem that practically all women, regardless of age, suffer during their menstrual cycle. However, the adolescent age group has the highest prevalence of women experiencing this. The symptoms of dysmenorrhea include pain in the lower abdomen extending to the waist that typically begins 2-3 days before menstruation and lasts for 1-2 days throughout menstruation, along with certain associated symptoms such as heartburn, pains, or prickles.1 The purpose of this study is to assess the effect of turmeric stew on the pain scale used to diagnose dysmenorrhea in students attending Senior High School 1 East Pamona, Poso Regency. With a total of 34 respondents, this study used the Quasy Experiment method with a non-randomized control group pre-posttest design and a purposive sampling strategy. The study's data were gathered utilizing general data collection sheets and NRS pain scale measurement sheets (Numeric Rating Scale). The Wilcoxon Signed Rank Test and the Mann Whitney U-Test were used to analyze the data. Before drinking turmeric stew, both the treatment and control groups had moderate pain. Meanwhile, the average pain intensity after drinking the turmeric stew was 68.8 % mild pain and 31.2 % no pain in the treatment group, and 37.5% mild discomfort and 62.5 % moderate pain in the control group. Following statistical analysis with the Wilcoxon Signed Rank Test, a p-value of 0,000 ≤ α 0,05was achieved, showing that turmeric stew affected both groups. Additionally, a statistical test utilizing the Mann-Whitney U-Test yielded a value of 0,000 ≤ α 0,05, showing a significant difference in pain scale reduction between the treatment and control groups. To summarize, ingesting turmeric stew has a substantial effect on lowering the pain scale for dysmenorrhea in students. Keywords: Turmeric stew, Dysmenorrhea, High school students